Fort Collins aggregate mine planning for closure: optimising post-closure land use through mine operations - Collyard, JS; Arigoni, M (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
The mine (name redacted at the request of the operator) is a construction material aggregate mine located outside of Fort Collins, Colorado, USA. Operating successfully for over 40 years, the mine is now nearing the end of its operational life. International Corporation assisted in the preparation of a mine planning update and vision that focused on meeting all regulatory obligations and optimising the post-closure land use. Understanding that the closure obligations are defined in the Colorado Land Reclamation Act for the Extraction of Construction Materials (Colorado Division of Reclamation, Mining and Safety [CDRMS] 2008) and in the Clean Water Act of 1972 (United States of America 1972). The CDRMS and the United States Army Corps of Engineers (USACE) project team worked collaboratively to evaluate, assess and develop a mine closure plan that delivers a project that not only meets regulatory requirements and is financially viable but is also socially and contextually conscious, and allows for the successful operation of the mine in its remaining years. An overview of the Clean Water Act of 1972 and USACE’s role is detailed at https://www.usace.army.mil/About/History/Historical-Vignettes/Civil-Engineering/155-Clean-Water-Act-Overview/. The existing mine property is uniquely situated within myriad land uses that include agriculture, commercial, institutional and residential applications. With the surrounding community context in mind, the potential postclosure land uses were evaluated for land value, compatibility, constructability, costs, an implementation schedule and future land use risks. Potential feasible post-closure land uses were defined and evaluated, including residential, commercial, wetland mitigation banking, agricultural, recreation and combinations of uses. This approach required a multidisciplinary team consisting of mining and civil engineers, landscape architects, ecology and wetland specialists, cost estimators, property valuation experts and permitting specialists. Conceptual closure alternatives were defined and evaluated, resulting in a combination of post-closure land uses. Although the selected alternative resulted in a reduction in aggregate to be mined, it was chosen based on the assessment of all criteria discussed above. This paper will present the process and alternatives, and the mine and closure plan as developed for the Timnath mine.
Keywords: post-closure land use